2020
DOI: 10.21608/jaauth.2020.45371.1079
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Employee Trust in the Relationship Between Leaders’ Aggressive Humor and Knowledge Sharing

Abstract: Purpose-The current paper aims to examine leaders' aggressive humor's influence on knowledge-sharing among hotel employees. Employee Trust is also tested as a moderator variable between this association. Design/methodology-An online questionnaire of 387 customer-contact employees of 38 five-star hotels located in Sharm El-Sheikh in Egypt provided data on the moderating role of trust in aggressive humor-knowledge-sharing relationships. Using the SEM by the PLS method by SmartPLS3 program, the data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This provides a nuanced understanding of the different effects of leader humor style on employee knowledge sharing. Meanwhile, our study answers the inconsistent conclusions regarding the positive effect of leader humor on employee knowledge sharing (Abdillah, 2021) and the negative effect of leader humor on employee knowledge sharing (Fayyad, 2020). Moreover, our study also contributes to the knowledge sharing literature by calling for a deep exploration of the influencing factors of employee knowledge sharing (Ahmad and Karim, 2019).…”
Section: Theoretical Implicationsmentioning
confidence: 48%
See 1 more Smart Citation
“…This provides a nuanced understanding of the different effects of leader humor style on employee knowledge sharing. Meanwhile, our study answers the inconsistent conclusions regarding the positive effect of leader humor on employee knowledge sharing (Abdillah, 2021) and the negative effect of leader humor on employee knowledge sharing (Fayyad, 2020). Moreover, our study also contributes to the knowledge sharing literature by calling for a deep exploration of the influencing factors of employee knowledge sharing (Ahmad and Karim, 2019).…”
Section: Theoretical Implicationsmentioning
confidence: 48%
“…First, there are few studies to investigate the link between leader humor and employee knowledge sharing, along with paradoxical findings. For instance, Fayyad (2020) revealed that leader humor negatively impacts knowledge sharing, whereas, Abdillah (2021) held that leader humor positively impacts knowledge sharing. These inconsistent findings underscore that future research will provide a nuanced understanding of the relationship between leader humor style and employee knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al and Vecchio et al [18,19] further argued that positive humor decreases employees' work withdrawal behavior and turnover intentions. Moreover, the results of the study [20] found that aggressive humor can enhance a hotel's knowledge-sharing culture if there is trust among employees.…”
Section: Theoretical Background and Hypotheses Development 21 Humor I...mentioning
confidence: 92%
“…To date, several studies have identified boosters of PCSP (Chen et al, 2017;Wu et al, 2020;Ye et al, 2019), whereas less attention has been paid to examining PCSP inhibitors, especially from the (Gu et al, 2019;Guenzi et al, 2019;He and Li, 2019;Huo et al, 2012;Lee, 2015;Liu et al, 2019;Mesmer-Magnus et al, 2018;Neves and Karagonlar, 2020;Trif and Fodor, 2019), little is known about its impact on the hospitality context. To the best of the authors' knowledge, Fayyad's (2020) study is the only study to explore the effect of LAH in the hospitality context. Our study extends the LAH literature by expanding its deleterious effects to the hospitality context, thereby addressing the call of Elkhwesky et al (2022) to better understand leadership in the hospitality context.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…LAH occurs when leaders express humour towards their subordinates in a hostile way to boost themselves (Martin et al , 2003), such as denigrating, disparaging, teasing or ridiculing employees. These forms of LAH have been found to yield negative consequences, including increased stress, emotional exhaustion, turnover intention, addictive behaviours and deviant behaviours, as well as decreased job satisfaction, affective commitment, organisational pride, job engagement, creativity, voice and knowledge-sharing behaviours (Fayyad, 2020; Gu et al , 2019; Guenzi et al , 2019; He and Li, 2019; Huo et al , 2012; Lee, 2015; Liu et al , 2019; Mesmer-Magnus et al , 2018; Trif and Fodor, 2019).…”
Section: Introductionmentioning
confidence: 99%